Peran Edukasi Perawat dengan Tingkat Pengetahuan pada Kejadian Anemia Ibu Hamil Trimester III: The Role of Nurse Education and the Level of Knowledge in the Incidence of Anemia in Pregnant Women in the Third Trimester - Nuryani Asiyah (MPI Press, 2022)
Background: Education is a planned effort to influence others, whether individuals, groups, families, or communities, in order to promote healthy living behaviors. Objective: This study aims to determine the role of nurse education on the level of knowledge regarding anemia incidence in pregnant women in the third trimester in the Emergency Room of RSIA Brawijaya Duren Tiga in 2020. Method: This research uses a cross-sectional approach with a total sampling technique. The total number of respondents is 35 pregnant women. The research instrument uses a questionnaire. Statistical analysis was conducted using the Chi-square test with a significance level of α 0.05. Results: The Chi-square test results show a relationship between the role of nurse education and the level of knowledge regarding anemia incidence in pregnant women in the third trimester at RSIA Brawijaya Duren Tiga, with a p-value of 0.013 < 0.05. Conclusion: There is a relationship between the role of nurse education and the level of knowledge regarding anemia incidence in pregnant women in the third trimester.